Evaluation of Ground Arthropod Structure in Restoration Area of Talangagung Landfill as Edutourism Attraction, Kepanjen, Malang - Azalia, Dinda; Setiawan, Hendra; Retnaningdyah, Catur (Journal of Indonesian Tourism and Development Studies, 2015)
Aim of this research is to know the composition, community structure and survivality of ground arthropod in restoration area of Talangagung edutourism landfill (TPA Wisata Edukasi Talangagung). Arthopod survey was conducted with four methods, yellow pan trap, pit fall trap, berlesetullgren, and sweep net. The research was done in four different locations with twice repetition. Survey location was devided in three zone, which is zone one with 10 years restoration, zone two with five years restoration, and zone three which not yet restored, and reference site. Abiotic factor which observed in this research such as light intensity, humidity, and air temperature. Analysis of arthropod diversity and community structure in each site was calculated from importance value index (IVI) and diversity index (Shannon Wienner Index). The results show that diversity of ground arthropod in zone one, two, three, and reference site was on medium level which each score 1.9, 1.87, 1.71, and 2.08. Community structure with dominant pattern showed with IVI from Acrididae in zone one and zone three with IVI 67.2 % and 53.5 %. Myrmicidae in reference site dominance with IVI 51.4 % and Formicidae in zone one with IVI 48.6 %. Ground arthropod in zone one and reference site had similarity in community structure which showed in same cluster in biplot analysis and zone two and three was in another different cluster. Keywords : Arthropod, diversity, restoration, community structure